IMPLIKASI HARMONISASI PERATURAN PERPAJAKAN TERHADAP PRINSIP KEADILAN VERTIKAL DAN HORIZONTAL DALAM SISTEM PERPAJAKAN NASIONAL - Dianasari, Sevi (Fakultas Hukum Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Abstract This study examines the implications of tax regulation harmonization on the principles of vertical and horizontal justice in the national taxation system, especially after the implementation of the Tax Regulation Harmonization Law (UU HPP) in the 2021-2025 period. Through a normative legal approach and qualitative analysis, this study identifies that the HPP Law has resulted in significant changes in the income tax rate structure, value added tax reformulation, the introduction of voluntary disclosure programs, and strengthening tax administration. The research findings indicate that harmonization efforts have improved vertical justice through the implementation of a more granular progressive rate structure and the expansion of the tax base for high-income groups. Meanwhile, improvements in horizontal justice are reflected in the equalization of tax treatment between the formal and informal sectors, as well as between various types of income. However, this study also identifies several challenges such as administrative complexity and the risk of non-compliance that can hinder the achievement of optimal tax justice. The research results recommend a strategy to strengthen the tax system through simplification of tax administration, strengthening the capacity of tax authorities, and educating taxpayers to ensure effective implementation of tax harmonization policies that support the principles of tax justice.